(3GdHWGdI hGdJVNe (B:s (3GdebhdGJ GdfXQjI hefGgL GdSjGSI GdGbJUGOjI (B/s - (3GdOHGZ, GSGeI HTjQs ((3YeGf(B: s (3OGQ GdGgdjI ddfTQ(B, s, 2007)
(3ebOeI(B-(3GdHGH GdChd (B: (3GdefGgL GdJbdjOjI aj GdJMdjd GdGbJUGOj Gdcdj (B: (3GdaUd GdChd (B: (3fehPL GdacQ GdcdGSjcj GdONd hGdYeGdI hGdEfJGL (B: (3eMOOGJ GdONd hGdYeGdI hGdEfJGL aj GdfehPL GdcdGSjcj (B: (3GdaUd GdKGfj (B: (3fehPL GdacQ GdcdGSjcj GdfXQjI GdcejI aj GdfbhO (B: (3GdfXQjI GdcejI cfXQjI aj GdCSYGQ (B: (3GdaUd GdKGdK (B: (3GdGfbdGH GdcjfRj (B: (3aQhV GdfehPL GdcjfRj (B: (3GdaUd GdQGHY (B: (3fehPL gcS hGdJhGRf GdGbJUGOj GdYGe (B: (3fehPL GdJhGRf GdGbJUGOj GdYGe (B: (3GdaUd GdNGeS (B: (3GdYeGdI hGdGSJNOGe ef GdefXhQ GdcjfRj (B: (3GdfXQjI GdcdGSjcjI aj GdJhXja (B: (3GdaUd GdSGOS (B: (3fehPL ajdHS hGdYdGbI Hjf GdJVNe hGdHWGdI (B: (3ajdHS hGdeYGOdI GdfGbUI(B-(3GdHGH GdKGfj (B: (3GdefGgL GdMOjKI aj GdJMdjd GdGbJUGOj Gdcdj (B: (3GdaUd GdSGHY (B: (3GdfXQjI GdfbOjI GdMOjKI (B: (3GdefgL GdJMdjdj ddfXQjI GdfbOjI (B: (3GdaUd GdKGef (B: (3fehPL ajdHS hGdJhbYGJ GdSYQjI (B: (3aGFV GdWdH Ydi GdYeGd hGdCLhQ GdMbjbjI (B: (3GdaUd GdJGSY (B: (3GdeOQSI GdcdGSjcjI GdMOjKI Hjf GdQTO haYGdjI GdSGSjI GdGbJUGOjI (B: (3Gdgjcd GdJMdjdj ddfXQjI GdcdGSjcjI GdMOjKI (B: (3GdaUd GdYGTQ (B: (3fXQjI GdOhQI GdJLGQjI GdMbjbjI (B: (3fXQjI GdOhQI GdJLGQjI GdMbjbjI ef GdefXhQ GdJGQjNj (B: (3GdaUd GdMGOj YTQ (B: (3GdeOQSI GdcjfRjI GdMOjKI (B: (3GdfXQjI GdcjfRjI GdMOjKI GdaQhV GdQFjSI(B.s
(3HjHdjhZQGajG U(B.434 (3agQS GdehVhYGJ hGdGYdGe U(B.448s
Keywords: (3EbJUGO cdjs; (3HWGdIs; (3JVNes